End-to-End Trust and Security for Internet of Things Applications. - Bhattarai, Sulabh; Wang, Yong (Computer (00189162), 2018)
Many Internet of Things (IoT) devices utilize the cloud to store data and synchronize with one another. Because data breaches can occur anywhere en route to the cloud, ensuring end-to-end trust and security for IoT applications is critical. The authors propose a novel 3D threat model for the IoT and discuss nine security and privacy challenges as well as several ways to mitigate risks.